2016
DOI: 10.1016/j.neuropharm.2016.06.023
|View full text |Cite
|
Sign up to set email alerts
|

Voluntary co-consumption of alcohol and nicotine: Effects of abstinence, intermittency, and withdrawal in mice

Abstract: Alcohol and nicotine are often used together, and there is a high rate of co-occurrence between alcohol and nicotine addiction. Most animal models studying alcohol and nicotine interactions have utilized passive drug administration, which may not be relevant to human co-addiction. In addition, the interactions between alcohol and nicotine in female animals have been understudied, as most studies have used male animals. To address these issues, we developed models of alcohol and nicotine co-consumption in male … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(41 citation statements)
references
References 50 publications
4
37
0
Order By: Relevance
“…In Experiment 2b, we found that chronic suppression of alcohol consumption with increasing concentrations of quinine increased both nicotine and water preference in male mice, and only increased nicotine preference in female mice. Our previous study showed that forced alcohol abstinence produced an enhancement in concurrent nicotine consumption and preference in male and female C57BL/6J mice (O'Rourke et al, 2016). Together with this study, our work showed that alcohol intake is unresponsive to the presence or absence of the nicotine bottle, but nicotine intake is influenced by the absence of alcohol consumption or by the adulteration of the alcohol bottle with quinine.…”
Section: Discussionsupporting
confidence: 80%
“…In Experiment 2b, we found that chronic suppression of alcohol consumption with increasing concentrations of quinine increased both nicotine and water preference in male mice, and only increased nicotine preference in female mice. Our previous study showed that forced alcohol abstinence produced an enhancement in concurrent nicotine consumption and preference in male and female C57BL/6J mice (O'Rourke et al, 2016). Together with this study, our work showed that alcohol intake is unresponsive to the presence or absence of the nicotine bottle, but nicotine intake is influenced by the absence of alcohol consumption or by the adulteration of the alcohol bottle with quinine.…”
Section: Discussionsupporting
confidence: 80%
“…Additionally, the effect of sazetidine-A has never been tested in mice, nor on voluntary, oral co-consumption of alcohol and nicotine presented concurrently. In this study, we tested the effect of sazetidine-A on alcohol and nicotine consumption in male and female mice using models of voluntary, oral consumption that we developed and have described previously (O’Rourke et al, 2016). Here, we show for the first time that sazetidine-A, at a dose that does not affect water or saccharin consumption, reduces alcohol consumption in mice without affecting nicotine consumption.…”
Section: Introductionmentioning
confidence: 99%
“…4 Similar sex differences have been observed in rodent models. Female C57BL/6 mice consume more alcohol and nicotine in a two-bottle choice procedure, 22 are less sensitive to nicotine-induced locomotor activity, and show more anxiogenic behavior in response to nicotine compared to male animals. 45 Sex hormones can modulate the reward system, and estradiol itself can influence gene transcription in neurons.…”
Section: Sex Differences In Nachr-dependent Behaviorsmentioning
confidence: 96%